Social identity processes trends in theory and research - Capozza, Dora.; Brown, Rupert, 1950- (London : SAGE, 2000)
Providing an overview of the latest developments in social identity theory from the leading scholars in the field, this volume addresses theoretical contributions, recent empirical assessments and applications of social identity theory.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Group identity